An Economic Evaluation of the TROG 99.03 Trial: Systemic Therapy After Radiotherapy in Early‐Stage Follicular Lymphoma - Daniel Erku; Joshua W. D. Tobin; John F. Seymour; Michael MacManus; Paul Scuffham; Greg Hapgood (eJHaem)
ABSTRACT Background The TROG 99.03 trial demonstrated improved progression‐free survival for patients with early‐stage follicular lymphoma (FL) treated with systemic therapy using rituximab‐cyclophosphamide, vincristine, prednisolone (R‐CVP) after involved‐field radiotherapy (RT) versus RT. As systemic therapy was associated with more acute toxicity, the possibility of long‐term toxicity, and no survival benefit yet, the cost‐effectiveness of RT+R‐CVP is important. Aim We performed a cost‐effectiveness analysis of RT (reference), RT+CVP, and RT+R‐CVP from the TROG 99.03 trial. Methods We constructed a Markov model (15‐year horizon) to compare treatments: RT (reference), RT+CVP and RT+R‐CVP from the 150 patients in the TROG 99.03 trial. Median follow‐up was 11.3 years (range: 4.4–17.8). Lifetime direct health care costs, quality‐adjusted life‐years (QALYs) and incremental cost‐effectiveness ratios (ICERs) were calculated. Australian dollars AUD$50,000 was defined as the proposed willingness‐to‐pay threshold (WTP). Results RT+R‐CVP was associated with an improvement of 0.711 QALYs compared to RT, 0.532 QALYs compared to RT+CVP, and was the dominant strategy. The costs of adverse events or retreatment for relapses or transformation had a minimal influence on the ICERs. Sensitivity analyses resulted in ICER values below the WTP with RT+R‐CVP remaining the dominant strategy. Conclusion RT+R‐CVP is clearly cost‐effective and was the dominant strategy in early‐stage FL compared to RT or RT+CVP as it delivers superior outcomes at a lower cost from the Australian tax‐payer's perspective. Trial Registration The authors have confirmed clinical trial registration is not needed for this submission